Tannin levels in the foliage of some Spanish shrub species at different stages of development - Ammar H.; López S.; González J.S.; Ranilla M.J. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Total extractable phenols (TEP), total extractable tannins (TET) and extractable condensed tannins (CT) were determined in the foliage of four Spanish indigenous shrub species from León uplands (North West Spain). To follow seasonal variations and different stages of development leaves were collected at different times of the year. According to CT, the shrub species were: E. australis greater than C. laurifolius greater than R. canina equal to Q. pyrenaica. In relation to the seasonal variations, extractable CT concentration was highest in summer for all species, except for E. australis, which was in autumn. Young leaves of Q. pyrenaica and C. laurifolius collected in spring had higher TEP and TET contents than in autumn, whereas the opposite trend was observed for R. canina leaves. Little seasonal differences in TEP and TET concentrations were detected in E. australis. Leaves of all species had high concentrations of these secondary compounds in all seasons, which may be an important constraint for the use of these plants by ruminants browsing upland areas where these shrub species are predominant.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)